Ontogeny and growth of marine shelled molluscs under climate change scenarious - Freitas, Daniela Bastos de (2022)
Marine organisms that produce biogenic carbonates, such as the shelled molluscs in Class Gastropoda and Bivalvia, are especially prone to be negatively affected by Ocean acidification (OA) and Warming (W). With shells composed of more soluble calcium carbonate polymorphs, these animals’ early life stages are potentially more vulnerable to OA-W, a serious problem as larval survival is crucial for the species’ persistence. In this sense, the prediction of the effects of OA-W in the early life of the marine shelled molluscs is extremely important for the assessment of the impacts of these phenomena on marine ecosystems. This thesis describes the combined effects of OA-W on the survival, ontogenic development, growth and integrity of the biogenic carbonates of the early life stages of two model species of high ecological and commercial importance, respectively, the gastropod Tritia reticulata and the bivalve Venerupis corrugata. The early larval stages of both species were exposed, for two months, to OA-W experimental scenarios, based on the latest projections of the Intergovernmental Panel on Climate Change (IPCC) for the end of the century. The results revealed an extreme vulnerability of T. reticulata planktonic larval stages to the simultaneous occurrence of OA-W, with severe mortalities, reduced growth rates, lower shells’ crystallinity, higher dissolution, and even shell loss after only 8 of days exposure to the most extreme scenario (22°C pHtarget 7.5). These results suggest dramatic effects of warming and ocean acidification on T. reticulata in early life, lessening considerably the chances of larvae to survive in the wild if projections become effective. In turn, the bivalve V. corrugata revealed an apparent resilience to OA-W under the tested conditions, with increased larval survival under warming and acidification (22°C pHtarget 7.6). In this species, the ontogenic development was clearly favoured by the temperature rise even under a significant antagonistic effect of the pH reduction on growth. However, even knowing that the applied experimental scenarios were not exactly the same and thus, it is not possible to directly compare the results obtained in both species, the pullet carpet shell V. corrugata was shown to be resilient to the tested scenarios. This makes V. corrugata a very promising resource for the aquaculture industry as it appears to be a species that may be able to cope with future environmental conditions of OA-W predicted until the end of this century.